Respons Pertumbuhan Bibit Kelapa Sawit Akibat Pengaturan Bobot Mulsa Tandan Kosong dan Frekuensi Penyiraman - Yan Sukmawan; Dewi Riniarti (Jurnal Penelitian Kelapa Sawit, 2020)
Lack of water is usually becomes a limiting factor for the growth of oil palm seedlings in main-nursery. This study was conducted to investigate the effect of the empty fruit bunch (EFB) mulch and watering frequency on the growth of oil palm seedlings maintained under main-nursery conditions. This study has been carried out in the nursery station of the Politeknik Negeri Lampung from April 2019 to September 2019, using completely randomized block design with two factor and three replications. The first factor is mulch weight (0 g, 100 g, 200 g, and 300 g) and the second factor is watering frequency (every day, every two days, and every three days). The results indicate that there are significant interactions between the EFB mulch and watering frequency on stem diameter, transpiration rate and photosynthesis rate of oil palm seedling. Application of 200 g and 300 g EFB mulch combined with watering frequency every two days and three days is able to produce the same stem diameter of oil palm seedling compared to the control. Low soil moisture around root of oil palm seedling causes photosynthesis and nutrients availability are reduced.